ChemInform Abstract: Diversity‐Oriented Synthesis of Drug‐Like Macrocyclic Scaffolds Using an Orthogonal Organo‐ and Metal Catalysis Strategy. Issue 17 (April 2015) - Grossmann, Andre; Bartlett, Sean; Janecek, Matej; Hodgkinson, James T.; Spring, David R.
Abstract Key features of the strategy are NHC‐mediated organocoupling and Grubbs‐catalyzed metathesis reaction.